2010
DOI: 10.1016/j.jep.2010.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic constituents and their potential anticancer activities from Devil's Club (Oplopanax horridus Miq.)

Abstract: Ethnopharmacological relevance-Devil's Club Oplopanax horridus (Sm.) Miq. is a widely used folk medicine in the Pacific Northwest such as Alaska and British Columbia for treating a variety of ailments including arthritis, cold, fever, infections, diabetes and cancer.Aim of the study-To investigate hydrophobic constituents and their potential anticancer activity from Devil's Club O. horridus. Materials and methods-The root bark of O. horridus (Sm.) Miq was isolated by chromatographic techniques. Structures of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 26 publications
2
37
0
Order By: Relevance
“…Previous work had reported that OH-1~4 exhibited potential anticancer acitives on human breast cancer and colon cancers through cell arrest in G2/M phase and induction of appoptosis at both earlier and later stages [17]. In this study, the potential mechanisms of the four new compounds OHR-1, -2, -3 and -5 with the strongest anti-proliferative activity among the series of acylated polyynes were investigated.…”
Section: Apoptosis and Cell Cycle Assaysmentioning
confidence: 94%
See 3 more Smart Citations
“…Previous work had reported that OH-1~4 exhibited potential anticancer acitives on human breast cancer and colon cancers through cell arrest in G2/M phase and induction of appoptosis at both earlier and later stages [17]. In this study, the potential mechanisms of the four new compounds OHR-1, -2, -3 and -5 with the strongest anti-proliferative activity among the series of acylated polyynes were investigated.…”
Section: Apoptosis and Cell Cycle Assaysmentioning
confidence: 94%
“…However, as the two acetylated polyynes had 18 carbon atoms in the main skeleton chain (C18 polyynes) while the others had 17 carbon atoms as the main structural chain (C17-polyynes). It seems that they could not be compared diretly together to reach that conclusion [17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 15 known compounds were identified as (+)-praeruptorin A (2) [20,21], (+)-praeruptorin B (3) [20,21], (+)-praeruptorin E (4) [20][21][22], selinidin (5) [23], cis-3′,4′-diisovalerylkhellactone (6) [19,24], pteryxin (7) [6], suksdorfin (8) [25,26], Pd-Ib (9) [27,28], qianhucoumarin D (10) [20,21], (+)-samidin (11) [25,[29][30][31], laserpitin (12) [32], (9R,10R)-9-acetoxy-8,8-dimethyl-9,10-dihydro-2H,8H-benzo [1,2-b:3,4-b′]dipyran-2-one-10-yl-ester (13) [33], bergapten (14) [34,35], xanthotoxin (15) [36], and falcalindiol (16) [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%